Rapid Assessment of Earthquake Threat Vulnerability in Campus 3 of University of Technology Yogyakarta Based on Android Application - Dwi Kurniati; Eka Faisal Nurhidayatullah; Samsul A Rahman Sidik Hasibuan (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
The province of D.I.Yogyakarta is crossed by the Indo-Australian Plate which is one of the three world plates. The impact that occurs when an earthquake happens is the damage to buildings not only simple buildings but also multi-story buildings, such as School Buildings and Educational Facilities. The Campus 3 of University of Technology Yogyakarta is located at Jl. Prof. Dr. Soepomo, S.H. No.21, Muja Muju, the sub district of Umbul Harjo, Yogyakarta. The purpose of this study is to determine the results of the evaluation using the RVS method on a form that is filled out manually and by an application using ArGis. The method used in this research is FEMA 154-2015 which is adjusted to the regulations in Indonesia, namely SNI 1726-2019, and the results are analyzed quantitatively. Based on the checking of vulnerability of the campus building with the RVS High Seismicity form, the campus 3 building is of the type of reinforced concrete frame and functioning as a school. The results obtained show that the average of two buildings in the Campus 3 of University of Technology Yogyakarta is 2.3, and the RVS stops at level 1. Both conditions confirm that the two buildings have a risk that is not dangerous. Nevertheless, there should be a further supervision.